Delayed onset of severe chronic pain in CASPR2 autoantibody–associated Morvan syndrome in a former UK swine abattoir worker. (September 2018) - Goebel, Andreas; Moore, Austen Peter; Jacob, Anu
Abstract: Introduction: Autoantibody-mediated autoimmunity directed against targets within the voltage-gated potassium channel complex (VGKCC autoantibodies) has been implicated in causing neuropathic pain. Methods: We report the case of a 76-year-old, United Kingdom male who was diagnosed with contactin-associated protein 2 (CASPR2) autoantibody–associated Morvan syndrome, a rare neurological condition. Results: He had previously worked in a swine abattoir; exposure to aerosol within swine abattoirs has been reported to elicit an immune response resulting in the production of these autoantibodies; however, unusually, his manifestations emerged with several years' latency. Although this patient's Morvan syndrome–associated seizures were well-controlled with antiepileptic drugs, his neuropathic pain and painful muscle fasciculations did not respond to pharmacological interventions. He refused pain management program treatment, but high-dose immunoglobulin treatment or treatment with rituximab, reported to be sometimes effective in this group, was not initiated because of concerns regarding his general frailty. Discussion and Conclusion: This case highlights issues around the identification and treatment of rare patients with chronic pain who have voltage-gated potassium channel complex autoantibodies; it also emphasizes the possibility that former swine abattoir workers might be at risk of developing neuropathic pain even years after their vocational exposure. Abstract : Supplemental Digital Content is Available in the Text.